A novel care pathway for prisoners with intellectual disability designed through a Delphi process. Issue 4 (17th December 2018) - Gulati, Gautam; Quigley, Stephen; Murphy, Valerie Elizabeth; Yacoub, Evan; Bogue, John; Kearns, Anthony; O'Neill, Conor; Kelly, Mary; Morrison, Aideen; Griffin, Gerard; Blewitt, Mary; Fistein, Elizabeth; et al.
Abstract : Purpose: Individuals with an intellectual disability (ID) form a significant minority in the Irish prison population and worldwide prison populations. There is growing recognition that specialist services for such individuals are in need of development. The purpose of this paper is to propose a care pathway for the management of individuals with an ID who present in prison, based on expert elicitation and consensus. Design/methodology/approach: A convenience sample of professionals with a special interest in forensic intellectual disabilities was invited to participate in a Delphi exercise. In total, 12 agreed to participation and 10 subsequently completed the study (83.3 per cent). Expert views were elicited using a semi-structured questionnaire. Content analysis was completed using NVivo 11 software. A care pathway was subsequently proposed, based on the outcomes of the analysis, and circulated to participants for debate and consensus. A consensus was reached on management considerations. Findings: Ten experts across a range of disciplines with a combined experience of 187 years participated in the study. Current provision of care was seen as limited and geographically variable. The vulnerability of prisoners with ID was highlighted. The need for equivalence of care with the community through multidisciplinary input and development of specialist secure and residential placements to facilitate diversion was identified. Consensus was achieved on a proposed care pathway. Originality/value: This study proposes a care pathway for the assessment and management of prisoners with an ID and is, therefore, potentially relevant to those interested in this topic internationally who may similarly struggle with the current lack of decision-making tools for this setting. Although written from an Irish perspective, it outlines key considerations for psychiatrists in keeping with international guidance and, therefore, may be generalisable to other jurisdictions.